2009
DOI: 10.1002/jbm.a.32351
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of insulin production from encapsulated islets to endotoxin‐stimulated macrophage inflammatory mediators

Abstract: Chronic inflammation may compromise function of implanted encapsulated islets. Increased purity of alginate used for encapsulation prolongs encapsulated graft function, correlating with decreased presence of impurities like bacterial endotoxin. Limits for endotoxin contamination in biomaterials based on indirect inhibition of function of embedded cells have yet to be established. In a coculture system with RAW 264.7 monocyte/macrophage cells in the presence of 50 ng/mL murine recombinant gamma-interferon (mrIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
(192 reference statements)
0
1
0
Order By: Relevance
“…Moreover, Lyle et al. reported that macrophages played an important role in both early and chronic inflammation following intraperitoneal microencapsulated islet transplantation. Thus, macrophages, HMGB1, TNF‐α, and IL‐6 may be therapeutic targets following intraperitoneal microencapsulated NPI xenotransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lyle et al. reported that macrophages played an important role in both early and chronic inflammation following intraperitoneal microencapsulated islet transplantation. Thus, macrophages, HMGB1, TNF‐α, and IL‐6 may be therapeutic targets following intraperitoneal microencapsulated NPI xenotransplantation.…”
Section: Discussionmentioning
confidence: 99%